Legal Resilience of Islamic Banking in Indonesia Amid Economic Crises - Solehoddin; Arya Sandi Yudha Libert; Ferio Ivan Mulyono (Universitas Brawijaya, 2026)
This article examines the legal resilience of Islamic banking in Indonesia during three major economic crises: the 1998 monetary crisis, the 2008 global financial crisis, and the COVID-19 pandemic. The central legal issue is whether the legal framework governing Islamic banking has sufficient normative capacity to maintain systemic stability during crises and how such capacity is shaped through regulatory adaptation. Previous studies by Susilawati et al. (2025), Candera and Indah (2020), and Anisa et al. (2025) predominantly analyse Islamic banking resilience using empirical, quantitative financial indicators, with limited attention to the legal and regulatory architecture as an autonomous object of normative analysis. This study addresses this gap by employing a normative juridical method with a historical approach to analyse statutory regulations, regulatory instruments, and Sharia governance mechanisms across crisis periods. The analysis is theoretically grounded in the theory of the legal system developed by Gunther Teubner. The findings show that the institutionalisation of Sharia principles within banking regulation functions as a normative constraint that stabilises normative expectations during economic crises. This study concludes that Islamic banking resilience in Indonesia is primarily shaped by the adaptive capacity of its legal system and offers insights relevant to jurisdictions with dual banking systems.